2018
DOI: 10.1139/cgj-2016-0614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying–wetting cycles on soil-water characteristic curve of undisturbed granite residual soils and microstructure mechanism by nuclear magnetic resonance (NMR) spin-spin relaxation time (T2) relaxometry

Abstract: Due to the formational environment and climatic variability, granite residual soils with grain-size distribution ranging from gravel to clay undergo multiple drying–wetting cycles. The influences of multiple drying–wetting cycles on the soil-water characteristic curve (SWCC) and pore-size distribution (POSD) of undisturbed granite residual soils are investigated using the pressure plate test and nuclear magnetic resonance (NMR) spin-spin relaxation time (T2) distribution measurement, respectively. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…e EMC was set as 17% in the test, and the cyclic amplitude of wetting-drying was considered as EMC ± 1%, EMC ± 3%, and EMC ± 5%. Since 2 Advances in Civil Engineering many studies [10,15,29,30] have reported that the in uence of wetting-drying cycles on the properties of soil is limited after 4 to 6 cycles, the maximum number of wetting-dryings was selected as ve cycles in this study. After each wettingdrying cycle, the dimensions of the specimen should be measured to calculate volumetric strain of specimens.…”
Section: Cyclic Wetting-dying Testmentioning
confidence: 99%
See 1 more Smart Citation
“…e EMC was set as 17% in the test, and the cyclic amplitude of wetting-drying was considered as EMC ± 1%, EMC ± 3%, and EMC ± 5%. Since 2 Advances in Civil Engineering many studies [10,15,29,30] have reported that the in uence of wetting-drying cycles on the properties of soil is limited after 4 to 6 cycles, the maximum number of wetting-dryings was selected as ve cycles in this study. After each wettingdrying cycle, the dimensions of the specimen should be measured to calculate volumetric strain of specimens.…”
Section: Cyclic Wetting-dying Testmentioning
confidence: 99%
“…Wetting-drying cycles can be treated as an alternative loading on the soil in form of suction along with the change of moisture content. So, the soil-water characteristic or hydromechanical behaviour is also studied [1,9,10]. e initial condition and suction path can affect the properties of soil subjected to cyclic wetting-dryings.…”
Section: Introductionmentioning
confidence: 99%
“…The time τ was equal to half of echo time. The CPMG pulse sequence used in this study was same as that in previously studies [43,[53][54][55]. It was testified the CPMG pulse sequence could be used to determine the value of T 2 of soil samples.…”
Section: Methodsmentioning
confidence: 99%
“…Much research has been conducted on the theoretical model of the SWCC. According to some studies, the SWCC is influenced by multiple factors, including temperature [37], drying and watering cycles [38][39][40], stress history [41,42], and initial density [43][44][45], in which the pore structure of the soil has a decisive influence on the SWCC [46][47][48][49]. Early SWCC models used the pore distribution coefficient to reflect the influence of the pore structure.…”
Section: Introductionmentioning
confidence: 99%